Management strategies for sport-related traumatic dental injuries: a systematic review based on case reports - Silva-Sousa, A. C.; Oliveira-Aguiar, J.; Paula-Silva, F. W. G.; Sousa-Neto, M. D.; Candemil, A. P. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Recent advancements in sports dentistry have emphasized the critical need for effective management and outcomes assessment of sports related dental injuries. The aim of this systematic review was to compile and analyze case reports and to explore various strategies in treating sports-related dental trauma and their outcomes.